TAFSĪR AL-KHATĪB AL-MAKKĪ: A Study of Sayyid 'Abd Al-Hamīd Ibn Ahmad Al-Khatīb's Interpretation of Juz Tabarak - Wahidi, Ridhoul; Halim, Abdul; Arifullah, Mohd (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
This research examines the characteristics of Tafsir al-Khatīb al-Makkī; Tafsir Juz Tabārak by Sayyid 'Abd al-Hamīd ibn Ahmad al-Khatīb. The writing of the title of this commentary is attributed to the name of his father, namely Shaykh Ahmad Khatib al-Minangkabawi, even though it was his son who wrote it. He was a scholar of Indonesian descent who was born, had a career and died in Arabia. Traces of his work and intellect, which are still little explored, are a contribution to completing the treasures of works by Indonesian ulama. Using library research and descriptive analysis, this article examines and analyzes the background to the preparation of the interpretation, methodology, and the advantages and disadvantages of the interpretation. The results of this research found that the preparation of this interpretation was motivated by the attitude of people who had ignored the benefits of the Al-Qur'an to the point that they had become backward among other nations. The interpretations that emerged did not accommodate the fast-paced conditions of the times. The ulama did not try to spread the message of Islam through the Qur’an in language that was simple and easy for everyone to understand. The preaching scholars are only concerned with fiqh issues. After long reflection on the religious spirit of Islam and the Muslim community, he wrote a comprehensive commentary entitled Tafsīr Al-Khatīb al-Makki. From the aspect of Tafsir sources, this book is classified as a Tafsir bi al-ma'sūr. The method used is the tahlilī method and the style used is adabi ijtimā'i and the systematics of writing Tafsir Juz Tabārak is tartib mushafi.